Education and inequality across Europe (Cheltenham, 2009)
"The relationship between education and income inequality is of fundamental importance. In this book, an international group of renowned contributors focus on patterns of inequality and their relationship to education using recent data from European countries. The fresh and unique research deals with important topics such as: wage and education inequality, differences in earnings related to gender, the role of labour market institutions, demographic and cohort effects on inequality, intergenerational education and income mobility, the extent of ‘overeducation’ and job and life satisfaction inequality.